1993
DOI: 10.2166/wst.1993.0324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Recovery of Cryptosporidium from Water

Abstract: Methods were evaluated for the recovery of Cryptosporidium oocysts from water. Various types of cartridge filter were tested but proved to be inferior to the standard Cuno Micro-Wynd filter. Laboratory scale sand columns were also evaluated. The retention within the column material was satisfactory at low flow rates. However, the system was judged inadequate for monitoring because of the poor retention of oocysts within the column matrix at realistic flow rates. The continuous flow centrifuges tested were show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…This appeared to be the case particularly in water samples containing low numbers of oocysts, such as treated waters, underground and spring waters. The recovery ef®ciency of the classical method currently used to detect waterborne oocysts has often been reported to be low and extremely variable (Whitmore and Carrington 1993;Jakubowski et al 1996). For example, the clari®cation of water samples by a Percoll±sucrose density gradient contributes signi®cantly to losses of cryptosporidial oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…This appeared to be the case particularly in water samples containing low numbers of oocysts, such as treated waters, underground and spring waters. The recovery ef®ciency of the classical method currently used to detect waterborne oocysts has often been reported to be low and extremely variable (Whitmore and Carrington 1993;Jakubowski et al 1996). For example, the clari®cation of water samples by a Percoll±sucrose density gradient contributes signi®cantly to losses of cryptosporidial oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to high variability in recovery efficiencies (Shepherd and Wyn-Jones 1995). Alternative methods involve flocculation with calcium carbonate (Vesey et al 1993), vortex flow filtration and cross-flow filtration (Whitmore and Carrington 1992). Some of these…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies (Hashimoto et al 2002;Abramovich et al 2001;Briancesco et al 1999) revealed the presence of oocysts in the samples examined. The explanation of these different results could be ascribed to the fact that the current concentration methods for the detection of Cryptosporidium oocysts are elaborate with variable recovery efficiencies (Whitmore and Carrington 1993;Nieminski and Ongerth 1995;Brandonisio et al 2000;Sunnotel et al 2006;Taguchi et al 2006). Moreover, high levels of turbidity can exert a detrimental effect on oocysts recovery or may interfere with oocysts detection.…”
Section: Discussionmentioning
confidence: 99%